"What is the actual goal of the pathway?": examining emergency department physician and nurse perspectives on the implementation of a pediatric concussion pathway using the theoretical domains framework - Anh Ly; Roger Zemek; Bruce Wright; Jennifer Zwicker; Kathryn Schneider; Angelo Mikrogianakis; Alf Conradi; David Johnson; Brenda Clark; Karen Barlow; Joseph Burey; Ash Kolstad; et al. (BMC, 2021)
Abstract Background Multiple evidence-based clinical practice guidelines (CPGs) exist to guide the management of concussion in children, but few have been translated into clinical pathways (CP), which operationalize guidelines into accessible and actionable algorithms that can be more readily implemented by health care providers. This study aimed to identify the clinical behaviours, attitudinal factors, and environmental contexts that potentially influence the implementation of a clinical pathway for pediatric concussion. Methods Semi-structured interviews were conducted from October 2017 to January 2018 with 42 emergency department clinicians (17 physicians, 25 nurses) at five urban emergency departments in Alberta, Canada. A Theoretical Domains Framework (TDF)-informed interview guide contained open-ended questions intended to gather feedback on the proposed pathway developed for the study, as well as factors that could potentially influence its implementation. Results The original 14 domains of the TDF were collapsed into 6 clusters based on significant overlap between domains in the issues discussed by clinicians: 1) knowledge, skills, and practice; 2) professional roles and identity; 3) attitudes, beliefs, and motivations; 4) goals and priorities; 5) local context and resources; and 6) engagement and collaboration. The 6 clusters identified in the interviews each reflect 2-4 predominant topics that can be condensed into six overarching themes regarding clinicians' views on the implementation of a concussion CP: 1) standardization in the midst of evolving research; 2) clarifying and communicating goals; 3) knowledge dissemination and alignment of information; 4) a team-oriented approach; 5) site engagement; and 6) streamlining clinical processes. Conclusion Application of a comprehensive, evidence-based, and theory-driven framework in conjunction with an inductive thematic analysis approach enabled six themes to emerge as to how to successfullly implement a concussion CP.